Revealing the hardening mechanisms of ion-irradiated nanostructured multilayers/substrate systems: A theoretical model. (March 2021) - Liu, Kai; Zhang, Boya; Long, Xiangyun; Deng, Huiqiu; Xiao, Xiazi; Jiang, Chao
Abstract: In this work, a mechanistic model is proposed for modeling the depth-dependent hardness of ion-irradiated nanostructured multilayers/substrate systems. Four dominant hardening mechanisms during the whole nanoindentation process are systematically analyzed, which include the indentation size effect (ISE) induced by geometrically necessary dislocations (GNDs), irradiation hardening determined by irradiation-induced defects, substrate effect and interface hardening existing within the multilayers. Thereinto, the former three are determined by the average density of dislocations and defects within the plasticity affected region (PAR), and are noticed to be affected by both the indentation depth and existing interface between the film and substrate layer. By considering the interface effect on both the geometrical shape and expansion ability of the PAR, the hardness-depth relation of ion-irradiated nanostructured multilayers/substrate systems is explicitly deduced at four different stages. Based on this model, the evolution of related microstructures in the film and substrate can be quantitatively analyzed, which involves the PAR, and average density of irradiation-induced defects and GNDs. The rationality and accuracy of the proposed model are validated by comparing the theoretical results with the experimental data, including two types of unirradiated systems (the YSZ/Al2 O3 multilayers/Si substrate and W/Si system) and an ion-irradiated YSZ/Al2 O3 multilayers/Si substrate system. The proposed model offers a promising way to qualitatively analyze other mechanical properties of ion-irradiated nanostructured multilayers/substrate systems. Graphical abstract: Image 1 Highlights: A mechanistic model with interface effect is proposed for ion-irradiated multilayer nanofilms/substrate systems. Contributions of dislocations, defects, unirradiated substrate and interfaces within the nanofilms are addressed in the model. Average density of dislocations and defects affected by the indentation depth and interface is addressed. Theoretical results with calibrated model parameters match well with corresponding experimental data.